Involvement and barriers towards provision of health promotion activities among nurses in Kuantan, Pahang - Ahmad Sabri, Farah Hanun; Makhtar, Aniawanis (IIUM Press, 2022)
Background: Nurses make up the single largest healthcare professional group in the Malaysian healthcare system. As frontline healthcare providers, they promote healthy lifestyles to patients and families. Nevertheless, the nurses encounter many barriers towards their involvement in providing health promotion activities. The aim of this study was to explore the nurses’ involvement and barriers towards the provision of health promotion activities.